2015
DOI: 10.1371/journal.pone.0144193
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gaze Position on Reaching Movements in an Obstacle Avoidance Task

Abstract: Numerous studies have addressed the issue of where people look when they perform hand movements. Yet, very little is known about how visuomotor performance is affected by fixation location. Previous studies investigating the accuracy of actions performed in visual periphery have revealed inconsistent results. While movements performed under full visual-feedback (closed-loop) seem to remain surprisingly accurate, open-loop as well as memory-guided movements usually show a distinct bias (i.e. overestimation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 49 publications
3
6
0
Order By: Relevance
“…The asymmetry in increasing safety margins between rightward and leftward 517 movements was unexpected. To explain this pattern of results it is noteworthy to emphasize that the 518 increase in trajectory curvature due to removing the visual feedback is much less for rightward 519 compared to leftward passes (the comparison between dotted line and solid line in Figure 6B), which is 520 also in accordance with previous findings ( Similarly, Ross et al (2015) observed that varying the fixation while the visual feedback was available 533 caused participants to veer away from the fixated obstacle as opposed to free viewing or central 534…”
Section: Adapted Behavior Resulted In the Same Collision Rate For Difsupporting
confidence: 86%
“…The asymmetry in increasing safety margins between rightward and leftward 517 movements was unexpected. To explain this pattern of results it is noteworthy to emphasize that the 518 increase in trajectory curvature due to removing the visual feedback is much less for rightward 519 compared to leftward passes (the comparison between dotted line and solid line in Figure 6B), which is 520 also in accordance with previous findings ( Similarly, Ross et al (2015) observed that varying the fixation while the visual feedback was available 533 caused participants to veer away from the fixated obstacle as opposed to free viewing or central 534…”
Section: Adapted Behavior Resulted In the Same Collision Rate For Difsupporting
confidence: 86%
“…Eye-movements resulting in voltage changes of about 10-20 microVolts could be reliably identified and correspond to eye-movements of about 2° of visual angle (depending on skin condition, tiredness, etc. of participants, see Ross, Schenk, & Hesse, 2015 for similar procedure). Eye-movements were re-calibrated after every block for each participant.…”
Section: Set-upmentioning
confidence: 99%
“…The general idea that the fixation point plays an important role in the determination of the prehensile movement patterns has support from a study conducted by Ross, Schenk and Hesse [ 27 ]. Ross, Schenk and Hesse found that obstacle avoidance behaviour was moderated by fixation position when participants were required to move their hands through a gap between two obstacles into a target area.…”
Section: Discussionmentioning
confidence: 99%